Tradisi Khataman Qur’an dan Nadhoman pada Pernikahan Masyarakat Muslim-Sunda (Studi Tradisi di Kampung Cibeber-Kiarapedes-Purwakarta) - Ela Sartika (Jurnal test, 2023)
This article is motivated by the existence of several traditions in the Sundanese-Muslim Community in conducting marriage. The series of traditions are considered very important to be carried out, including in the village of Cibeber, Kiarapedes, Purwakarta Regency. However, an additional tradition for the Sundanese-Muslim community in the village after the marriage contract is carried out is closed by khatam Qur’an and reading the nadhoman as a prayer and advice for the bride and groom which is carried out by a group of people. The purpose of this research is as a form of traditional documentation and to describe the meaning contained in the implementation of the khatam Qur’an and nadhoman marriage which are usually carried out in the village. This study uses a qualitative approach in the realm of cultural anthropology and uses the theory of the living Qur’an with the main focus of its research on the Sundanese-Muslim community in Cibeber village, Kiarapedes district, Purwakarta regency. The result of this study consists of several points, including the first in the tradition of khatam Qur’an as a thanksgiving of the bride and groom as this tradition was carried out around 1800. Second, this marriage nadhoman was composed of Kiai using the Sundanese language of being a form of preaching and advice. Third, the reading of the nadhoman contains prayers and advice for the bride and groom which is taken from the contents of the verses in the Qur’an and the Hadits of the Prophet Muhammad which are arranged in the form of a nadhoman. Fourth, the meaning of this activity has religious, educational, dakwah, social and cultural meanings.